Sociometrics and human relationships : analyzing social networks to manage brands, predict trends, and improve organizational performance /: analyzing social networks to manage brands, predict trends, and improve organizational performance. (2017) - Gloor, Peter A (Peter Andreas), 1961-
No abstract available